2022
DOI: 10.1007/s10942-022-00475-x
|View full text |Cite|
|
Sign up to set email alerts
|

Can Rational Emotive Behaviour Therapy (REBT) and Mindfulness be Integrated Effectively within High Performance Settings?

Abstract: Our critical commentary explores the overlaps and divergences between Rational Emotive Behaviour Therapy (REBT) and contemporary mindfulness practice and considers whether the approaches could be integrated and applied effectively within two high performance settings in particular: sport and business. It highlights how REBT and mindfulness share similar philosophical positions on the causes of emotional disturbance, on the importance of acceptance, and on cultivating self-awareness to respond healthily and ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…In high performance settings, while important prerequisites to performance may involve physical and skill proficiency, the cognitive mechanisms at play may help distinguish the elite performers, and help distinguish subpar and superior performances (e.g., Saint-Martin et al, 2020) however more research is required to understand the role of beliefs in translation to behavior in high performance settings. REBT may be in a unique position to enhance psychological performance within high performance settings (Young et al, 2022). We have seen a recent emerging literature of REBT research within high performance settings (see Jordana et al, 2020 for a systematic review) but most of this has been in the context of sport 2022;Young et al, 2022).…”
Section: The Science Of Rebt As It Relates To Performance: Are We In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In high performance settings, while important prerequisites to performance may involve physical and skill proficiency, the cognitive mechanisms at play may help distinguish the elite performers, and help distinguish subpar and superior performances (e.g., Saint-Martin et al, 2020) however more research is required to understand the role of beliefs in translation to behavior in high performance settings. REBT may be in a unique position to enhance psychological performance within high performance settings (Young et al, 2022). We have seen a recent emerging literature of REBT research within high performance settings (see Jordana et al, 2020 for a systematic review) but most of this has been in the context of sport 2022;Young et al, 2022).…”
Section: The Science Of Rebt As It Relates To Performance: Are We In ...mentioning
confidence: 99%
“…REBT may be in a unique position to enhance psychological performance within high performance settings (Young et al, 2022). We have seen a recent emerging literature of REBT research within high performance settings (see Jordana et al, 2020 for a systematic review) but most of this has been in the context of sport 2022;Young et al, 2022). As such, below we present the accounts of six REBT performance psychology researchers as to their views pertaining to the current and future status of the science of REBT as it relates to performance.…”
Section: The Science Of Rebt As It Relates To Performance: Are We In ...mentioning
confidence: 99%
“…That is, REBT adopts a GABCDE framework, through which specific REBT addresses B (irrational beliefs) as the main purpose of the work, whilst general REBT can address all aspects of the framework, not just B. Thus, using general REBT one can apply a broad range of CBT derived techniques aligned with PST, and even mindfulness (e.g., Young et al, 2022). In the current case study, this general REBT approach was necessary in order to address the broader issues that were affecting the athlete.…”
Section: Model Of Practicementioning
confidence: 99%
“…Traditionally known as a non-judgmental, nonreactive awareness of one's present moment experience (Kabat-Zann, 1990), the utilisation of mindfulness in applied sport psychology practice can facilitate athletes becoming aware of personal thoughts and feelings while enhancing concentration on performance skills and strategies instead of performance outcomes (Pineau, Glass & Kaufman, 2014). Interestingly, according to Young et al (2022), some scholars, including Albert Ellis, have noted similarities between the teaching of mindfulness and REBT and have suggested that they may have integrative potential (e.g., Ellis, 2005Ellis, , 2006Whitfield, 2006). This has been evidenced in other psychology disciplines.…”
Section: Model Of Practicementioning
confidence: 99%
“…in 2010-2020; it is 68% more [13][14][15] . The average cost of living for a person with an eating disorder has increased by 29% over the decade, from $7,300 to $9,400 [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%